2011
DOI: 10.1017/s0022215111002866
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular coiling of a mycotic external carotid artery pseudoaneurysm following pharyngolaryngectomy with a free jejunal graft

Abstract: In this patient, endovascular coiling of the external carotid artery was considered to be the only definitive treatment for a life-threatening mycotic pseudoaneurysm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Pseudoaneurysm, also known as “false aneurysm”, is a hematoma contained by adventitia or perivascular tissue of an artery that results from a tangential injury to the vessel [ 5 ]. Most often it is secondary to penetrating trauma [ [6] , [7] , [8] ] or surgery. It is also a well-known iatrogenic complication of vascular catheterizations [ 3 , 9 ] and percutaneous procedures like biopsy of solid organs [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pseudoaneurysm, also known as “false aneurysm”, is a hematoma contained by adventitia or perivascular tissue of an artery that results from a tangential injury to the vessel [ 5 ]. Most often it is secondary to penetrating trauma [ [6] , [7] , [8] ] or surgery. It is also a well-known iatrogenic complication of vascular catheterizations [ 3 , 9 ] and percutaneous procedures like biopsy of solid organs [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study done at the Ninth People's Hospital, Shanghai Jiao Tong University concluded coil embolization by angiography of pseudoaneurysms coming off the external carotid artery is a useful alternative to standard surgical repair and avoids morbidity associated with performing surgery in the face and neck area [ 2 ]. Many case reports have also documented success of endovascular embolization of pseudoaneurysms of the ECA and its branches [ 6 , 7 ]. In our case, we have shown that glue can also be used to successfully resolve a pseudoaneurysm endovascularly.…”
Section: Discussionmentioning
confidence: 99%